Frequency and significance of HIV-1 infection of CD8+ T-cells: Implications for viral pathogenesis - Gulzar, Naveed (University of Ottawa (Canada), 2008)
To date, the effect of HIV-1 infection on CD8+ T-cells remains poorly studied. Previous studies have shown that the effector functions of CD8+ T-cells diminish during AIDS. We postulated that CD8+ T-cell functions decrease due to the tropism of HIV-1 for CD8+ T-cells. Therefore we examined whether CD8+ T-cells provide suitable targets for HIV-1 infection and the mechanism(s) by which the virus enters the cells. We hypothesized that HIV-1 entry into these cells may be facilitated through access to extracellular receptors. Ex vivo experiments were performed using blood samples from a cohort of HIV-1 infected patients attending the Ottawa Hospital Immunodeficiency Clinic. Frequency of HIV-1 infection was monitored by flow cytometric detection of HIV-1 p24 antigen and viral production from separated CD8+ and CD4+ T-cell lineages was assayed by the quantitation of viral RNA transcripts. Primary CD8+ T-cells and CD8+ T-cell clones used in the in vitro studies were isolated from the peripheral blood of healthy volunteers. HIV-1 infection was monitored by both ELISA and flow cytometric analyses. Similarly, receptor analysis was performed by flow cytometry and confirmed by RT-PCR analysis. There was a significantly higher frequency of CD8+HIV+ cells than CD4+HIV+ cells found in the ex vivo studies of patient samples, however, viral production from the CD8+HIV+ subset was 2-3 logs lower than that found in CD4+HIV+ T-cells. In addition, CD8+ T-cells served as suitable targets for productive HIV-1 infection in vitro and preferential HIV-1 replication occurred in the memory T-cell subset. Interestingly, the HTLV-I transformed CD8+ T-cell clones exhibited HIV-1 production 20-fold greater than CD4+ T-cells. Our research also demonstrated that during the course of infection, there was a decrease in mean expression of the CD8 and CXCR4 cell-surface molecules in the HIV-1 infected CD8+ T-cell clones. Accordingly, the use of antibodies to the CD8 or CXCR4 molecules eradicated viral adsorption and replication in the CD8+ T-cell clones. Our research was the first to demonstrate the significance and susceptibility of CD8+ T-cells to HIV-1 infection through both ex vivo and in vitro analyses. We conclude, with multiple lines of evidence detecting and measuring HIV-1 infection of CD8+ T-lymphocytes, that this cellular target and reservoir may be central to HIV-1 pathogenesis. By identifying a novel target of HIV-1 and potential cellular receptors used by the virus, future therapeutic strategies may be designed to help prevent and treat HIV-1 infection.
Keywords: Biology, Virology.